Systematic mapping of telehealth features for Autism Spectrum Disorder children: a preliminary results - Zakaria, Noor Azura; Tajuddin, Nur Syazwana; Mohd Supian, Nur Faraayuni Sufea; Fatah Yasin, Mohammad Dhiya’ul Hafidh; Lutfiani, Ninda; Ahmad, Nurul Shuhada (2024)
People with ASD typically have difficulty with social communication and interaction, learning disabilities and difficulty paying attention. Technologies currently being developed for Autism Spectrum Disorder (ASD) focus more on children’s behavioral development. Parents and caregivers of children with autism face greater challenges than typically developing children. In addition, parents with ASD children experienced serious psychological problems such as anxiety and depression, especially during Covid-19, as their children were limited to attend therapy sessions that usually take place in the therapy center. It is also a challenge for parents to cope with their children daily. Hence, supporting them to manage this issue through a telehealth platform is crucial to improve their psychological well-being. Therefore, the objective of this research is to identify the features related to telehealth for ASD children that were used in the previous study. The literature search was conducted using the online database which is IEEE Xplore. The number of 35 studies was reduced to 9 after conducting the screening processes. The final 9 studies were selected that highlighted the features of telehealth for ASD children. Therefore, the expected outcome from this research is to classify all the identified features and modules into their specific categories. It is hoped that further studies may lead to an effective digital intervention platform for better development of ASD children, which could assist parents and caregivers manage their ASD children in behavioral, communication, educational, and other aspects.